Identification Of Covid-19 Patients' Effect On Education Outcomes In Islam Majority Student Using Spatial Analysis - Ilyas Husti; Alwizar Alwizar; Zamsiswaya Zamsiswaya; Asmal May; Amril Mansur; Makhfuzat Makhfuzat; Khairil Anwar (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
The COVID-19 epidemic has had an impact on the educational landscape, particularly the move to a remote learning model utilizing internet media. This system has so many issues that we need to do an extensive educational assessment of the subject. In order to create an educational map of the mathematics learning scores of the Islam Majority Student population during the COVID-19 epidemic in SMP Pekanbaru City, Indonesia, this study used spatial analysis. The distribution of the number of patients who tested positively was related to the geographical analysis of the learning score. The majority of the city's western and eastern regions had few patients and did not improve the score for mathematics education, according to a comparison of the two maps. On the other hand, a small percentage of the northern and western regions revealed that the few patients raised the Mathematics education score. A tiny portion of the southern region discovered that the score for mathematics education fell as the proportion of positive patients rose. Furthermore, the fewest patients are found in tree-lined, deserted locations, yet there are still few schools there. In Pekanbaru City, the majority of the schools are still located in urban areas devoid of pleasant open spaces.